Use of photobiomodulation therapy associated with bovine bone matrix and heterologous fibrin biopolymer in the process of bone defect reconstruction - Rosso, Marcelie Priscila de Oliveira (2020)
In view of the challenges encountered after a tissue loss, methods that help in the reconstruction of bone tissue arouse interest in health research. The interaction between photobiomodulation therapy (PBMT) and bioproducts creates new perspectives on the success of tissue repair, such as, for example, the heterologous fibrin biopolymer (HFB) that can be associated with lyophilized bovine bone matrix (BM) in bone defects. Objective: In article 1, the objective was to systematically review the literature regarding the interaction of PBMT with bovine bone and, in article 2, to evaluate the effect of PBMT on the reconstruction of tibial defects with lyophilized bovine bone associated or not with the heterologous fibrin biopolymer. Materials and methods: In article 1, PubMed / MEDLINE, Web of Science and Scopus databases selected articles resulting from the combination of the keywords: Bovine bone AND low-level laser therapy, Bovine bone AND photobiomodulation therapy, Xenograft AND low-level laser therapy and Xenograft AND photobiomodulation therapy. In article 2, thirty male Wistar rats (Rattus norvegicus) were randomly separated into three groups, of 10 animals each, which after anesthesia were submitted to a 2 mm non-critical tibial defect. Groups received the following treatments: Group 1: BM + PBMT, Group 2: BM + HFB and Group 3: BM + HFB + PBMT. Animals in Groups 1 and 3 were submitted to PBMT in the immediate postoperative period and every 48 hours until the day of euthanasia that occurred at 14 and 42 days. Results: In article 1, the search in the three databases retrieved 240 articles, 18 of which met the established inclusion criteria. In studies in research animals (17 articles), PBMT assists in osteoconduction related to biomaterials, formation of new bone, bone healing, expression of immunomarkers, increase in collagen fibers and reduction of local inflammation. A human study demonstrated that the association of PBMT with bovine bone was effective for periodontal regeneration. In article 2, histomorphometric analysis showed a statistical difference in the percentage of bone formation between groups 3 (BM + HB + PBMT) and 2 (BM + HFB) (26.4% ± 1.03% and 20.0% ± 1.87%, respectively) at 14 days and at 42 days (38.2% ± 1.59% and 31.6% ± 1.33%, respectively) and at 42 days there was bone with mature characteristics, and organized connective tissue. Computed microtomography (CT) demonstrated BM particles filling the defect and depositing new bone in the superficial region of the ruptured cortex. Conclusion: The association of PBMT with HFB and BM improves the process of reconstruction of bone defects. In addition, the HFB favors the manipulation, insertion and permanence in the defect of the xenogenic graft.